Chloroplasts Isolation from Chlamydomonas reinhardtii under Nitrogen Stress - Yang, Miao; Jiang, Jun-Peng; Xie, Xi; Chu, Ya-Dong; Fan, Yan; Cao, Xu-Peng; Xue, Song; Chi, Zhan-You (Frontiers in Plant Science, 2017)
Triacylglycerols are produced in abundance through chloroplast and endoplasmic reticulum pathways in some microalgae exposed to stress, though the relative contribution of either pathway remains elusive. Characterization of these pathways requires isolation of the organelles. In this study, an efficient and reproducible approach, including homogenous batch cultures of nitrogen-deprived algal cells in photobioreactors, gentle cell disruption using a simple custom-made disruptor with mechanical shear force, optimized differential centrifugation and Percoll density gradient centrifugation, was developed to isolate chloroplasts from Chlamydomonas reinhardtii subjected to nitrogen stress. Using this approach, the maximum limited stress duration was 4 h and the stressed cells exhibited 19% and 32% decreases in intracellular chlorophyll and nitrogen content, respectively. Chloroplasts with 48 – 300 μg chlorophyll were successfully isolated from stressed cells containing 10 mg chlorophyll. These stressed chloroplasts appeared intact, as monitored by ultrastructure observation and a novel quality control method involving the fatty acid biomarkers. This approach can provide sufficient quantities of intact stressed chloroplasts for subcellular biochemical studies in microalgae.